2005
DOI: 10.1159/000086755
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis following Postanoxic Myoclonus Status epilepticus

Abstract: Prediction of outcome after cardiac arrest has important ethical and socioeconomic implications. In general, delay in recovery of neurological function is associated with a worse prognosis. The presence of myoclonic seizures early after anoxia has been identified as a poor prognostic factor. We report a series of patients who developed postanoxic myoclonus status epilepticus (MSE), which was defined as continuous myoclonic seizure activity lasting 30 min or more. The results from 18 patients were retrieved, 11… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
49
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(54 citation statements)
references
References 45 publications
4
49
0
1
Order By: Relevance
“…When persistent, acute post-hypoxic myoclonus is sometimes termed myoclonic status epilepticus or myoclonus status. The prognosis of patients with myoclonus status is extremely poor and must influence the decision to withdraw life support when present in comatose patients after cardiac arrest, 18,19 but careful evaluation allowed for more cautious optimistic outcome in this case. The development of myoclonus can also occur well after the initial insult, which has been known as Lance-Adams syndrome.…”
Section: Discussionmentioning
confidence: 94%
“…When persistent, acute post-hypoxic myoclonus is sometimes termed myoclonic status epilepticus or myoclonus status. The prognosis of patients with myoclonus status is extremely poor and must influence the decision to withdraw life support when present in comatose patients after cardiac arrest, 18,19 but careful evaluation allowed for more cautious optimistic outcome in this case. The development of myoclonus can also occur well after the initial insult, which has been known as Lance-Adams syndrome.…”
Section: Discussionmentioning
confidence: 94%
“…We've demonstrated a 100% mortality rate in NCSE post-cardiac arrest, independent of various treatment efforts such as hypothermia (39%) and IV anaesthetic infusions (72%). Others have also shown that patients with NCSE following cerebral anoxia almost invariably have a fatal outcome [36][37][38][39]. The same holds true for postanoxic generalized myoclonus, despite the successful use of propofol infusions to control elecographic seizure activity [40].…”
Section: Discussionmentioning
confidence: 97%
“…Myoclonus in the first few days after hypoxic brain damage is in general considered to predict an unfavorable prognosis in patients who remain comatose after cardiopulmonary resuscitation (CPR) 1, 2, 3. The incidence of posthypoxic myoclonus (PHM) in resuscitated patients with postanoxic encephalopathy (PAE) is 19%, and only 9–14% of these patients recover with mild to no cognitive deficits 4, 5, 6…”
Section: Introductionmentioning
confidence: 99%